Pengaruh Mata Kuliah Metode Matematika terhadap Keterampilan Merancang Masalah Cerita Penjumlahan dan Pengurangan pada Calon Guru SD - Mulyani, Ucu Agustini Sri (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study aims to investigate the impact of a mathematics methods course on prospective elementary school teachers' skills in designing word problems involving addition and subtraction. A total of 55 participants took part in a quasi-experimental study with a repeated-measures design, in which they were asked to create word problems before and after completing the unit “Developing Meaning for Mathematical Operations.” The generated problems were analyzed using a theoretical framework that categorizes structures of addition and subtraction problems, and statistically tested using one-way ANOVA. The results showed an increase in the diversity and complexity of problem structures designed after the intervention. This reflects the effectiveness of meaning-oriented instruction in enhancing prospective teachers’ problem-posing abilities. These findings highlight the importance of integrating problem-posing skills into teacher education curricula to better prepare future teachers to teach mathematical operations meaningfully in elementary classrooms.ABSTRAKPenelitian ini bertujuan untuk menyelidiki pengaruh mata kuliah metode matematika terhadap keterampilan calon guru sekolah dasar dalam merancang masalah cerita penjumlahan dan pengurangan. Sebanyak 55 peserta mengikuti desain kuasi-eksperimental dengan pengukuran berulang, diminta merancang masalah cerita sebelum dan setelah menyelesaikan unit "Mengembangkan Makna untuk Operasi Matematika." Masalah yang dihasilkan dianalisis menggunakan kerangka teori struktur masalah penjumlahan dan pengurangan, dan diuji secara statistik dengan ANOVA satu arah. Hasil menunjukkan peningkatan keragaman dan kompleksitas struktur masalah yang dirancang setelah intervensi. Ini mencerminkan efektivitas pengajaran berbasis makna dalam memperluas kemampuan problem-posing calon guru. Hasil ini menunjukkan pentingnya integrasi keterampilan problem-posing dalam kurikulum pendidikan guru, untuk mendukung kesiapan mereka mengajarkan operasi matematika secara bermakna di kelas.